Chemotherapy associated dural sinus thrombosis presenting as a cerebrospinal fluid leak. Issue 6 (1st June 2020) - Bujoreanu, Iulia; Ferguson, Mark; Saleh, Hesham
Abstract : Despite the well documented increased risk of thrombosis in patients with cancer and during chemotherapy, cerebral venous sinus thrombosis (CVT) remains a rare entity. We present a rare case of cerebrospinal fluid (CSF) rhinorrhoea secondary to a left transverse sinus thrombus which occurred 2 years previously during chemotherapy for breast cancer. The patient underwent a three-layer repair using Neuro-Patch, septal cartilage and middle turbinate pedicle flap and was started on acetazolamide. There was no recurrence at 1-year follow-up. Raised intracranial pressure secondary to cerebral venous occlusion can erode the base of skull and predispose to CSF leaks. Despite the theoretical risk, there have been no cases reported where CSF leaks have occurred following chemotherapy induced CVT. We describe the first case and discuss pathophysiology and management.